Antiferroelectrics: History, fundamentals, crystal chemistry, crystal structures, size effects, and applications. Issue 8 (6th May 2021) - Randall, Clive A.; Fan, Zhongming; Reaney, Ian; Chen, Long‐Qing; Trolier‐McKinstry, Susan
Abstract: Antiferroelectric (AFE) materials are of great interest owing to their scientific richness and their utility in high‐energy density capacitors. Here, the history of AFEs is reviewed, and the characteristics of antiferroelectricity and the phase transition of an AFE material are described. AFEs are energetically close to ferroelectric (FE) phases, and thus both the electric field strength and applied stress (pressure) influence the nature of the transition. With the comparable energetics between the AFE and FE phases, there can be a competition and frustration of these phases, and either incommensurate and/or a glassy (relaxor) structures may be observed. The phase transition in AFEs can also be influenced by the crystal/grain size, particularly at nanometric dimensions, and may be tuned through the formation of solid solutions. There have been extensive studies on the perovskite family of AFE materials, but many other crystal structures host AFE behavior, such as CuBiP2 Se6 . AFE applications include DC‐link capacitors for power electronics, defibrillator capacitors, pulse power devices, and electromechanical actuators. The paper concludes with a perspective on the future needs and opportunities with respect to discovery, science, and applications of AFE.